Tumpang Tindih Peran dan Wewenang Lembaga Penyelenggara Pemilu dan Lembaga Peradilan Dalam Proses Pembatalan Calon dan Penundaan Pelaksanaan Pemilihan Kepala Daerah - Ihsan Mazhumi (Politeia: Jurnal Ilmu Politik, 2018)
The election of the Governor and Deputy Governor, Regent and Deputy Regent and Mayor and Vice Mayor are the first in Indonesia to be held on December 9, 2015. A total of 269 regions comprising 9 provinces, 36 cities and 224 districts or about 53 percent of the total 537 provinces and districts in Indonesia will conduct the first wave elections.However, not all regions can vote simultaneously on December 9, 2015. A total of 5 districts have to be postponed for voting because PT TUN or MA has not issued a dispute related ruling in the five areas. The five areas are Central Kalimantan Province, Fakfak Regency (Papua), Manado City (North Sulawesi), Pematangsiantar and Simalungun (North Sumatra).